Terapi Bermain Menggambar Efektif Menurunkan Kecemasan Anak 3–6 Tahun Akibat Hospitalisasi: Effective Drawing Play Therapy Reduces Anxiety in Children Aged 3-6 Years Due to Hospitalization. - Ramadhan, Fahla; Jumari; Yuliza, Emi (Journal of Nursing Education and Practice, 2022)
Background: Hospitalization is required when patients experience physical, psychological, or social changes or disruptions. Hospitalization in children can have various impacts, such as separation-related sadness, loss of emotional control, pain, non-cooperativeness, depression, and more. According to a maternal and child health survey, out of 1,425 hospitalized children, 33.2% experienced severe stress, 41.6% mild stress, and 25.2% experienced no stress. Objective: This study aims to examine the effect of drawing play therapy on preschool-aged children (3-6 years) with hospitalization-induced anxiety during inpatient care at the hospital. Method: The research design employs a Quasi-Experimental approach with a one-group pre-test post-test design. The sample consists of 20 respondents, and data collection instruments include anxiety questionnaires, interviews with the parents of pediatric patients, and documentation sessions. Results: Univariate data analysis revealed that the average age of the child respondents was 4.35 years, with 8 boys (40%) and 12 girls (60%). Bivariate analysis indicated that drawing play therapy had a significant effect on preschool-aged children (3-6 years) with hospitalization-induced anxiety during inpatient care at the hospital, with a p-value of 0.000. Conclusion: Based on the results of the conducted research, it can be concluded that drawing play therapy has an effect on preschool-aged children (3-6 years) with hospitalization-induced anxiety during inpatient care at the hospital.